2013
DOI: 10.2106/jbjs.l.01577
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Treatment for the Prevention of Scoliosis in Children with Duchenne Muscular Dystrophy: Long-Term Follow-up

Abstract: The long-term use of the glucocorticoid results in a substantial decreased need for spinal surgery to treat scoliosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 20 publications
3
89
0
5
Order By: Relevance
“…There is evidence that using steroids in patients with DMD can have numerous positive effects including prolonged independent ambulation, decreased progression of scoliosis, increased muscle strength, respiratory function, cardiac function and quality of life (18,(21)(22)(23)(24)(25)(26). The use of steroid therapy has been associated with a reduction in the incidence of scoliosis in DMD because prolonging ambulation means that some boys will undergo their pubertal growth spurt before loss of ambulation.…”
Section: Interventions Before Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that using steroids in patients with DMD can have numerous positive effects including prolonged independent ambulation, decreased progression of scoliosis, increased muscle strength, respiratory function, cardiac function and quality of life (18,(21)(22)(23)(24)(25)(26). The use of steroid therapy has been associated with a reduction in the incidence of scoliosis in DMD because prolonging ambulation means that some boys will undergo their pubertal growth spurt before loss of ambulation.…”
Section: Interventions Before Surgerymentioning
confidence: 99%
“…The use of steroid therapy has been associated with a reduction in the incidence of scoliosis in DMD because prolonging ambulation means that some boys will undergo their pubertal growth spurt before loss of ambulation. There is also evidence that suggests patients treated with long-term steroids may avoid developing a scoliosis (24).…”
Section: Interventions Before Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons between the natural history studies in the pre-glucocorticoid era and those after glucocorticoid therapy have demonstrated benefits in the motor function, giving longer independent gait, better core stabilization and upper limb function, prevention of spine deformities, and delaying the settlement of lower limb deformities [32][33][34][35][36][37][38][39] . The use of glucocorticoids is also responsible for nonmotor benefits, particularly in preserving respiratory function, preventing cardiomyopathy, improving quality of life parameters and prolonging life itself 38,40,41 .…”
Section: Are Glucocorticoids Recommended For Dmd Patients?mentioning
confidence: 99%
“…Il existe deux protocoles principaux : l'un utilisant le deflazacort (Calcort ® ) à une posologie de 0,9 mg/kg/jour (0,8 mg/kg à partir de 10 ans, 0,55 mg/kg à partir de 15 ans et 0,5 mg/kg au-delà de 18 ans) [3] ; l'autre utilisant la prednisone (Cortancyl ® ) : 0,75 mg/kg/jour pendant 6 mois à 1 an, puis 0,75 mg/kg un jour sur 2 pendant 1 à 2 ans [4]. Les effets primaires de la corticothérapie sont multiples : recul de l'âge de perte de la marche de 12 à 14,5 ans [5] ; amélioration de la fonction ventilatoire [6] ; âge d'apparition de la cardiomyopathie différé (15,2 ans versus 13,1 ans) [7] ; diminution du risque de scoliose (20 % vs 92 %) [8] ; réduction du taux de mortalité [9]. Les effets secondaires observés sont ceux d'une corticothé-rapie classique : fractures osseuses et tassements vertébraux, surpoids, retard statural, cataracte (infraclinique), troubles du comportement, hyperphagie, syndrome cushingoïde, hirsutisme, troubles gastriques [3].…”
unclassified